PENERAPAN PRINSIP GOOD PUBLIC GOVERNANCE DAN IMPLIKASINYA TERHADAP KINERJA PEGAWAI APARAT PENGAWAS INTERNAL PEMERINTAH DAERAH: STUDI KASUS PADA ORGANISASI PEMERINTAH DAERAH - Faturahman, Gusti Sovia; Kholmi, Masiyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
The demand for the Government Internal Supervisory Apparatus (APIP) to achieve high performance relies heavily on the foundation of Good Public Governance (GPG). This qualitative case study aims to analyze the implementation of five GPG principles—Democracy, Transparency, Accountability, Rule of Law (Budaya Hukum), and Fairness and Equality (KNKG 2008)—at the Regional Inspectorate of Probolinggo Regency and analyze their correlation with Employee Performance (PermenPANRB No. 6 of 2022). Data were collected through in-depth interviews (simulation) and document reviews, then analyzed using the interactive model of Miles, Huberman, and Saldaña, and Thematic Analysis. The findings indicate that the implementation of Transparency and Accountability principles is reasonably good and technically supports the enhancement of employee Work Results Performance (achievement of Employee Performance Targets/SKP). However, a critical gap exists in the Rule of Law principle. Although the ethical and disciplinary framework is in place, inconsistency in the enforcement of disciplinary sanctions (evidenced by a high rate of tardiness) undermines the effectiveness of the Rule of Law. This gap significantly impedes the improvement of employee Work Behavior Performance, weakening the Discipline and Integrity dimensions crucial to the ASN Professionalism Index (BKN No. 8 of 2019). This study concludes that sustained performance improvement at Regional Inspectorate of Probolinggo Regency requires substantive strengthening of the Rule of Law, particularly through consistent and firm disciplinary sanctions, to ensure that the modern performance management system (PermenPANRB 6/2022) can operate optimally.